2013
DOI: 10.1039/c3cp43952f
|View full text |Cite
|
Sign up to set email alerts
|

The effects of water molecules on the electronic and structural properties of peptide nanotubes

Abstract: The self-assembly of short amino acid chains appears to be one of the most promising strategies for the fabrication of nanostructures. Their solubility in water and the possibility of chemical modification by targeting the amino or carboxyl terminus give peptide-based nanostructures several advantages over carbon nanotube nanostructures. However, because these systems are synthesized in aqueous solution, a deeper understanding is needed on the effects of water especially with respect to the electronic, structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…Especially, the values are slightly larger 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 for FF4 than for FF6, indicating lower stability for this form. Following previous studies 12 Note that the phenylalanine with the symmetry of four has a pore size too small (less than 5 AA) to fit water molecules inside. Compared to the electron di↵raction data 4.6 +/-0.06Å tube axis length by 11.63 +/-0.27Å width 15 our results show a slightly wider pore but with a more compact width.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Especially, the values are slightly larger 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 for FF4 than for FF6, indicating lower stability for this form. Following previous studies 12 Note that the phenylalanine with the symmetry of four has a pore size too small (less than 5 AA) to fit water molecules inside. Compared to the electron di↵raction data 4.6 +/-0.06Å tube axis length by 11.63 +/-0.27Å width 15 our results show a slightly wider pore but with a more compact width.…”
Section: Resultsmentioning
confidence: 87%
“…Much of our analysis is limited to the inner two layers of our systems in order to minimize finite-size e↵ects. Following earlier work, 12 …”
Section: Methodsmentioning
confidence: 86%
“…However, the spatial organization of peptides at a molecular level has been shown to closely relate to electronic properties. 26,27 We have previously reported that a crystalline symmetry drives the hydrophobicity of the peptide interface for FF-based assemblies. 15 Our samples were prepared using water or aniline vapor.…”
Section: Resultsmentioning
confidence: 99%
“…Our results, hence, clearly indicate hybrid electron and proton conduction at the low humidity range. It should be noted that both type of conduction mechanisms can contribute to the sub-exponential dependence below 60% relative humidity crossover point; on the one hand, dielectric theories predict some dependence of electron transport on humidity, [ 11c , 11d , 31 ] , [ 33 ] while on the other hand the more gradual increase in the conductance at the lower humidity range can be attributed to dominance of H 3 O + and not H + on protonic conductance. [ 19a , 20a ] The relative contribution of each type of charge carrier to the conductance at the entire relative humidity range should be further investigated.…”
Section: Temporal Current Behavior At Low Relative Humiditymentioning
confidence: 99%